Pengaruh Pengembangan Karier Dan Motivasi Terhadap Kinerja Karyawan Pada PT Gading Propertindo Di Tangerang - Natasya Natasya; Fathorrahman Fathorrahman (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. The purpose of this study is to determine the magnitude of the influence of career development and motivation on Employee Performance at PT Gading propertindo in Tangerang both partially and simultaneously. The method used is quantitative. The sampling technique used was saturated sampling with a total sample of 54 respondents. The data collection technique in this study was to use a questionnaire that was shared online through a google form. Data analysis using validity test, rability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination and hypothesis test using SPSS (Statistical Package for Social Sciense) version 26. The result of this study is that career development has a significant effect on employee performance with the regression equation Y = 10.374 + 0.714 X1. The correlation value of 0.704 means that the two variables have a strong relationship with a coefficient of determination of 70.4%. The hypothesis test was obtained t count > the table (8.538 > 1.983). Thus H0 is rejected and H1 is accepted meaning that there is a significant influence between career development on employee performance. Work motivation has a significant effect on employee performance with the regression equation Y = 6.278 + 0.823 X2. The correlation value of 0.770 means that the two variables have a very strong relationship rate with a coefficient of determination of 77.0%. The hypothesis test obtained t count > t table (7.157 > 1.637). Thus H0 is rejected and H2 is accepted meaning that there is a significant influence between motivation on employee performance. The influence of career development and work motivation has a significant effect on employee performance with the regression equation Y = 2.000 + 0.358 X1 + 0.358 X2. The correlation value of 0.816 means that the free variable with bound variable has a very strong level of relationship with a coefficient of determination of 81.6% while the remaining 18.4% is influenced by other factors. Hypothesis Test obtained F count > F table or (50,695 > 2,300). Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between career development and motivation on employee performance at PT Gading Propertindo in Tangerang Keywords: Career Development, Motivation and Employee Performance